i. Here, A = 2a and B = 3b

∴ (2a – 3b)^{2} = (2a)^{2} – 2 × 2a × 3b + (3b)^{2} …. [(A – B)^{2} = A^{2} – 2AB + B^{2} ]

= 4a^{2} – 12ab + 9b^{2}

ii. Here, a = 10 and b = y

(10 + y)^{2} = 102 + 2 × 10xy + y^{2} …. [(a + b)^{2} = a^{2} + 2ab + b^{2} ]

= 100 + 20y + y^{2}

iii. Here, a = and b = q/4

(p/3 + q/4)^{2} = (p/3)^{2} + 2 x p/3 x q/4 + (q/4)^{2}…. [(a + b)^{2} = a^{2} + 2ab + b^{2} ]

iv. Here, a = y and b = 3/y

(y - 3/y)^{2} = y^{2} - 2 x (y) x 3/y + (3/y)^{2} …. [(a – b)^{2} = a^{2} – 2ab + b^{2}

= y^{2} - 6 + 9/y^{2}